A RECEPÇÃO DA TEOLOGIA DE DIETRICH BONHOEFFER NA AMÉRICA LATINA - Ramos, Luciana Soares (2007)
To chose the theme the reception of Bonhoeffer in the Latin America, the intention is to problemitize the influence exerted by the german Theologian Dietrich Bonhoeffer in Latin America Theology, treating it as a from of arrival of the texts on the latin american land, but also of its Reading, Selection and Critical re-writing until the day when we complete its birth. The investigation is considered to make it visible to what in its message and or is a biography and in a way enthuses to latin american generation of Young theologians, protestants and catholics from the mid-centuries. It became a basic place for the Superior School of Theology (EST), the IECLB, to the ecumenical Superior Evangelic Institute of Theological Studies of Buenos Aires, Argentina (ISEDET) also to an organization called Church and Society (ISAL). The privileged basic material was the production of registered theology in its collection of periodic magazines respectively. Theological Studies and Theology Books and Christianity and Society. However some of the theological catholics are analyzed, amongst them are Gustavo Gutiérrez, Jon Sobrino, Juan Luis Segundo and Frei Betto, texts that bring to light the influence of the caribbean theology besides other material that evidence old and new interpreters. The concepts that mobilizes this research : speech, as expressed by Michel Foucault and Eni Orlandi, memory from Maurice Halbwacks e Jacques Le Goff, dialect,. Leandro Konder, marks, Carlo Ginzburg, phenomenology, Husserl,Heidegger, and image and imaginary, Castoriadis.(AU)